Kagome Flatbands for Coherent Exciton-Polariton Lasing - Harder, Tristan H.; Egorov, Oleg A.; Krause, Constantin; Beierlein, Johannes; Gagel, Philipp; Emmerling, Monika; Schneider, Christian; Peschel, Ulf; Hoefling, Sven; Klembt, Sebastian (ACS Photonics, 2021)
Kagome lattices supporting Dirac cones and flatband dispersions are well-known as a highly frustrated, two-dimensional lattice system. Particularly, the flatbands therein are attracting continuous interest based on their link to topological order, correlations, and frustration. In this work, we realize coupled microcavity implementations of Kagome lattices hosting exciton-polariton quantum fluids of light. We demonstrate precise control over the dispersiveness of the flatband as well as selective condensation of exciton-polaritons into the flatband. Subsequently, we focus on the spatial and temporal coherence properties of the laserlike emission from these polariton condensates that are closely connected to the flatband nature of the system. Notably, we find a drastic increase in coherence time due to the localization of flatband condensates. Our work illustrates the outstanding suitability of the exciton-polariton system for detailed studies of flatband states as a platform for microlaser arrays in compact localized states, including strong interactions, topology, and nonlinearity.
CRIS-Team Scopus Importer:2023-04-20
Keywords: coherence; exciton-polariton; flatband lasing; flatbands; Kagome lattice; polariton condensation